Hysteresis Control 3-Level SI-NPC Inverter with Wind Energy System - K. Selvakumar; R. Palanisamy; K Vijayakumar; D Karthikeyan; D. Selvabharathi; V. Kubendran (Institute of Advanced Engineering and Science, 2017)
The system is a 3-level Neutral point clamped hysteresis current controlled Inverter with Wind energy as power source. The input DC Power for the multi-level inverter is drawn from wind turbine generator connected through a rectifier circuit. An inductor has been introduced for smoothening the DC output from the rectifier. The inverter uses Neutral Point Clamped topology. The switching pulses for the inverter are achieved by hysteresis current control technique. This system is advantageous over the conventional SPWM based system as the hysteresis current control allows to reduce the low frequency harmonics while also allowing to control the fundamental amplitude depending on frequency. The outputs for the system are verified using MATLAB simulations. The hardware for Hysteresis current control for the inverter is implemented by using a dSPIC microcontroller. The proposed system can be implemented in households for supplying backup power in case of power shortage and can also be used as a primary power source if wind flow is abundant. It is easy to implement, economical and provides clean energy